Strategies for Driving Good Governance in Basic Education School - Pholar, Sombat; Kenaphoom, Assoc. Prof. Dr. Sanya Kenaphoom; Kosolkittiampo, Assoc. Prof. Dr. Soawalak (Journal for Developing the Social and Community, 2017)
Governance is the latest Public Administration Paradigm focusing on efficiency and effectiveness in Public Management. This is defined in a concrete manner by the Office of the Prime Minister on the establishment of business management system. The good society and society 1999, and the Royal Decree on Good Corporate Governance 1999, consist of six elements: the rule of law, the morality, the transparency, the participation, the accountability and the worthiness. However, basic education is one of the government's tasks that need to be governed following the Good Governance, in keeping with the real goals of Public Management. Therefore, the strategies to promote Good Governance in basic education institutions should be consisted of 12 strategies were; (1) infrastructure development, (2) resource management development, (3) organization management development, (4) financial and budget management, (5) academic and services management, (6) student development, (7) external sector relationship management, (8) quality development, (9) virtue integrate promotion, (10) teacher development, (11) performance management development and (12) the learning society development.